Application of alternative educational methods in education of teachers for theology - Bencéné Fekete, Andrea (Acta Scientiarum Socialium, 2012)
Application of alternative educational methods in education of teachers for theology In theological education the most common form of teaching is lecture, both towards children and adults – this is preferred not just by the teachers, but also by the students. It is a general view that within the limited time-frame of distant education this is the best way of transmitting the most information and aiding the work of students at home. The methods applied in the education of adults needs to be different, of course, from those of the schools; however the alternative methods based on activity and achievement can be applied in this field as well. Theological teachers – after finishing their studies – will make sessions for children and adults about the Bible. The primary aim of the course would be to provide something differ-ent from â€˜forced’ learning. A good way of achieving this is to teach the teachers about the alternative methods and make them practice as well – this is why within the frames of differentiating pedagogy the adults are taught the same way as well. They get to know the stories of the Bible via project works, which make the scenes more authentic and understandable.